A simulation study of the size and power of Cochran’s Q versus the standard Chi-square test for testing the equality of correlated proportions - Gayle, Suelen S. (Kansas State University, 2010)
The standard Chi-square test for the equality of proportions of positive responses to c specified binary questions is valid when the observed responses arise from independent random samples of units. When the responses to all c questions are recorded on the same unit, a situation called correlated proportions, the assumptions under which this test is derived are no longer valid. Under the additional assumption of compound symmetry, the Cochran-Q test is a valid test for the equality of proportions of positive responses. The purpose of this report is to use simulation to examine and compare the performance of the Cochran-Q test and the standard Chisquare test when testing for the equality of correlated proportions. It is found that the Cochran-Q test is superior to the Chi-square test in terms of size and power, especially when the common correlation among the binary responses is large.
Keywords: Cochran's Q; Chi-Square; Binary Correlated Proportions; Power; Statistics (0463)